Will bank interest rate deregulation jeopardize economic growth? A case study of South Korea - Philippa S. Dee (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1984)
The first purpose of this paper is to demonstrate, as a theoretical.proposition, that elimination of controls on bank interest rates would not necessarily lead to a decline in output in those sectors which were previously able to obtain cheap bank credit, The efficiency gains obtained by eliminating these controls need not, therefore, come at the expense of economic growth (or whatever other benefits were presumed to accrue by fostering particular sectors using credit controls). The key to this result lies in a proper understanding of the way in which credit price control and quantity rationing in the regulated sector affects resource allocation, given the existence of a dual, unregulated financial sector. The second purpose of this paper is to present quantitative estimates of the macroeconomic and sectoral effects of the removal of bank interest rate controls in South Korea. In many ways the Korean experience is tailor-made for a study of this kind.
Keywords: 330